(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Â Background: Arterial stiffness is an independent predictor for vascular diseases. Carotid-femoral pulse wave velocity (CFPWV) is a reliable index of arterial stiffness. In the present study, we investigated the possible risk factors involving CFPWV in hypertension and diabetes mellitus (DM) subjects. Methods: 425 subjects (M/F 168/257) from Shougang Corporation Examination Center were divided into four groups: healthy group (n=185), hypertension group (n=135), DM group (n=32), hypertension with DM group (n=73). CFPWV was measured by Complior apparatus. Results: Our results showed that CFPWV was significantly higher in hypertension subjects with DM than in healthy and hypertension group, respectively (12.00+2.57 vs 10.12+2.28 m/s; 12.00+2.57 vs 10.78+2.07 m/s, both p<0.05). CFPWV was positively correlated with age, systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), fasting plasma glucose ( FBG), HbA1c, uric acid, Log NT-proBNP and Log Urine Albumin (microalbumin) Excretion [Log UAE] in the entire group(r=0.437, 0.410, 0.206, 0.423, 0.210, 0.275, 0.130, 0.135, 0.166, all p<0.05, respectively). Multivariate analysis showed that age, body mass index, SBP, PP, FBG were independent associating factors of CFPWV in all subjects (Î²=0.287, p<0.001; Î²= -0.194, p=0.003; Î²=0.223, p=0.001; Î²=0.293, p<0.001; Î²=0.161, p=0.008; respectively). Conclusions: Our present study suggested that CFPWV was significantly higher in hypertension subjects with DM compared to healthy and hypertension groups. Keywords: Carotid-femoral pulse wave velocity; Hypertension; Diabetes mellitus